Central banking at the frontier : creating a digital financial landscape - Moenjak, Thammarak (Emerald Publishing Limited, 2024)
With a foreword by Sethaput Suthiwartnarueput, Governor of the Bank of Thailand. Digital disruption is rapidly transforming the financial sector, propelled by FinTech, BigTech, and non-bank institutions meeting public needs but challenging incumbents. Central banks must adapt to facilitate fair competition, protect customer rights, and integrate new technology. Initiatives in countries like India, Brazil, and Thailand have reshaped finance, enhancing accessibility. Future developments, including central bank digital currencies, may revolutionize financial infrastructures, enabling incumbents and new players to offer improved products and services. Central Banking at the Frontier: Creating a Digital Financial Landscape: Architecting the New Digital Financial Landscape comprehensively explores these changes, providing insights into emerging issues, initiatives, and debates that will define the evolving financial landscape. Relevant not only for central bankers but also for professionals in banks, FinTech, and academia, Central Banking at the Frontier: Creating a Digital Financial Landscape helps readers stay informed on the dynamic digital era and contribute to shaping technology-driven financial services for the benefit of society.